Catalyst-on-hotspot nanoarchitecture: plasmonic focusing of light onto co-photocatalyst for efficient light-to-chemical transformation - Chong, Carice (2024)
Plasmon-mediated catalysis utilizing hybrid photocatalytic ensembles promises effective light-to-chemical transformation, but current approaches suffer from weak electromagnetic field enhancements from polycrystalline and isotropic plasmonic nanoparticles as well as poor utilization of precious co-catalyst. Here, efficient plasmon-mediated catalysis is achieved by introducing a unique catalyst-on-hotspot nanoarchitecture obtained through the strategic positioning of co-photocatalyst onto plasmonic hotspots to concentrate light energy directly at the point-of-reaction. Using environmental remediation as a proof-of-concept application, the catalyst-on-hotspot design (edge-AgOcta@Cu2 O) enhances photocatalytic advanced oxidation processes to achieve superior organic-pollutant degradation at ≈81% albeit having lesser Cu2 O co-photocatalyst than the fully deposited design (full-AgOcta@Cu2 O). Mass-normalized rate constants of edge-AgOcta@Cu2 O reveal up to 20-fold and 3-fold more efficient utilization of Cu2 O and Ag nanoparticles, respectively, compared to full-AgOcta@Cu2 O and standalone catalysts. Moreover, this design also exhibits catalytic performance >4-fold better than emerging hybrid photocatalytic platforms. Mechanistic studies unveil that the light-concentrating effect facilitated by the dense electromagnetic hotspots is crucial to promote the generation and utilization of energetic photocarriers for enhanced catalysis. By enabling the plasmonic focusing of light onto co-photocatalyst at the single-particle level, the unprecedented design offers valuable insights in enhancing light-driven chemical reactions and realizing efficient energy/catalyst utilizations for diverse chemical, environmental, and energy applications.